Environmental Burden of Disease due to Emissions of Hard Coal- and Lignite-Fired Power Plants in Germany - Michaela Liebig-Gonglach; Lina Neunhäuserer; Jeroen Kuenen; Barbara Hoffmann; Vanessa Soppa; Volker Diegmann; Claudia Hornberg (Frontiers Media S.A., 2023)
Objectives: The study estimated the environmental burden of disease (EBD) attributable to a long-term exposure of the population to nitrogen dioxide (NO2) and fine particulate matter (PM2.5) emissions from hard coal- and lignite-fired power plants in Germany for the year 2015.Methods: The contribution of coal-fired power plants to the total air pollutant concentration was modelled using a chemical transport model and then combined with population data to assess the corresponding population exposure. We calculated years of life lost (YLL), years of life with disability, or disability-adjusted life years for different health outcomes with a strong evidence for an association with the exposure.Results: The burden of disease from PM2.5 emissions from lignite is 1.2 times higher than that from hard coal emissions (7,866 YLL compared to 6,412 YLL). NO2 emissions from lignite, cause a burden of disease 2.3 times higher than hard coal NO2-emission (13,537 YLL compared to 5,906 YLL). The EBD for both pollutants is dominated by diseases of the cardiovascular system.Conclusion: Abandoning energy generation by coal-fired power plants would lower the burden of disease in Germany.